A Atividade De Ensino Do Professor De Matemática Do Sexto Ano: Sentidos Da Prática Docente - Branco, Adriane Romero [UNIFESP] (2018)
The Present Research Has As Title: "The Teaching Activity Of Sixth Grade Mathematics Teacher: Directions Of Teaching Practice" Aimed To Investigate The Organization Of Mathematics Teaching By Sixth Grade Teachers And Their Relation To The Meanings Attributed By These Teachers, The Specificities Of The Teaching Activity And The Learning Activity In This Stage Of Basic Education. The Theoretical Frameworks Adopted Involve The Historical-Cultural Perspective And, In Particular, The Theory Of Activity. We Adopted As A Method Of Investigation Historical Dialectical Materialism, Through A Formative Experiment That Was Objectified In Twenty-Two Meetings With A Singular Group Of Sixth-Grade Mathematics Teachers. In Order To Be Able To Observe The Movement Of The Senses Attributed By The Teachers, It Was Proposed Situations Triggering Learning, Based On The Concept Of Teaching Activity, So That Teachers, In The Collective, Appropriated Elements That Constitute The Specificities That Involve The Universe Of The Six Gra